Association of PPP1R1B polymorphisms with working memory in healthy Han Chinese adults - Ma, Hui; Qiu, Riyang; Zhang, Wenya; Chen, Xiaohong; Zhang, Liguo; Wang, Man (Frontiers in Neuroscience, 2022)
Aims: The dopamine- and cAMP-regulated phosphoprotein (DARPP-32), which is encoded by the PPP1R1B gene, plays a converging regulatory role in the central nervous system by mediating the actions of dopamine, serotonin, and glutamate. Previous studies have demonstrated that variations in genes related to the dopamine system influence working memory. The present study thus investigated whether polymorphisms in PPP1R1B gene were associated with working memory. Methods: A sample of 124 healthy Han Chinese were genotyped for three single nucleotide polymorphisms of PPP1R1B gene, namely rs12601930C/T, rs879606A/G, and rs3764352A/G, using polymerase chain reaction and restriction fragment length polymorphis manalysis. Working memory performance was assessed using the Wisconsin Card Sorting Test (WCST). Results: Significant differences were observed in the Total Correct (TC), Total Errors (TE), and Conceptual Level Responses (CLR) scores of the WCST among the three rs12601930C/T genotypes (p=0.044, 0.044, and 0.047, respectively); in TC, TE, Non-Perseverative Errors (NPE), and CLR scores between participants with the CC and (CT+TT) rs12601930C/T polymorphism genotypes (p=0.032, 0.032, 0.019, and 0.029, respectively); in TC, TE, Perseverative Errors (PE), NPE, and CLR scores between participants with the (CT+CC) and TT rs12601930C/T polymorphism genotypes (p=0.001, 0.001, 0.011, 0.004, and 0.001, respectively); and in NPE and CLR scores between participants with the GG and (AG+AA) genotypes of the rs3764352A/G polymorphism (p=0.011 and 0.010). Furthermore, for males only, there were significant differences in TC, TE, PE, NPE, and CLR scores among the rs12601930C/T genotypes (p=0.020, 0.020, 0.037, 0.029, and 0.014, respectively) and NPE and CLR scores among the rs3764352 genotypes (p=0.045 and 0.042). Conclusions: PPP1R1B gene polymorphisms rs12601930C/T and rs3764352A/G might be associated with working memory assessed by the WCST in healthy Chinese adults, especially among males.